Abreaction for conversion disorder: systematic review with meta-analysis - (:unkn) unknown (ROYAL COLLEGE OF PSYCHIATRISTS, 2010)
Background The value of drug interviews in the treatment of conversion disorder is at present unknown. Aims To review all the available papers published in English that report on the use of drug interviews for treating conversion/dissociative disorder. Method Databases (including EMBASE, MEDLINE and PsycINFO) were searched from 1920 to 2009. Selected publications had to report on the use of drug interviews in people diagnosed with a conversion/dissociative disorder. Qualitative and quantitative data were extracted. Predictors of a positive response were ascertained using meta-analytic techniques. Results Fifty-five papers meeting inclusion criteria were identified. No studies compared the intervention with a suitable control group. However, two studies reported high response rates when drug interview was used in individuals with treatment-resistant conversion disorder. In the meta-analysis, the use of suggestion and occurrence of emotional catharsis during the interview were positively associated with recovery. Combining two medications and comorbid psychiatric disorder were negatively associated with recovery. Conclusions The evidence for effectiveness of drug interviews is of poor quality but it may be of benefit in the treatment of acute and treatment-resistant conversion disorder. A proactive approach during the interview, making suggestions the individual will respond, could influence outcome. Comorbid psychiatric disorder should be treated conventionally. Experimental studies to determine efficacy are required.
Keywords: AMYTAL INTERVIEW; AMOBARBITAL INTERVIEW; FOLLOW-UP; DISSOCIATIVE DISORDER; PSYCHOGENIC AMNESIA; HYSTERIA; SYMPTOMS; LORAZEPAM; MEMORIES; DIAZEPAM